Numerical investigation of fractional finite viscoelastic model for soft solid food - Talib, Ahmad Tarmezee; Parid, Dzieda Muhamad; Mohammed, Mohd Afandi P.; Wakisaka, Minato (Elsevier, 2026)
This work examines the viscoelastic behaviour of soft solid foods, focusing on two modelling approaches: traditional Prony series and fractional viscoelastic models. While the Prony series efficiently captures material behaviour, its complexity often requires numerous parameters. In contrast, the fractional viscoelastic model offers a more compact representation with fewer parameters. Experimental tensile tests on chewing gum were conducted to benchmark the models' performance. Results revealed that the fractional model captures the tensile-relaxation data with fewer parameters than the Prony series. Simulations of extrusion and sheeting processes, and tensile micromechanics highlighted the fractional model's stability in capturing complex mechanical responses involving large strains and microstructural heterogeneity.